Building ESP Content-Based Materials to Promote Strategic Reading - Bautista Barón Myriam Judith (Universidad Nacional de Colombia, 2013)
This article reports on an action research project that proposes to improve the reading comprehension and vocabulary of undergraduate students of English for Specific Purposes-explosives majors, at a police training institute in Colombia. I used the qualitative research method to explore and reflect upon the teaching-learning processes during implementation. Being the teacher of an English for specific purposes course without the appropriate didactic resources, I designed six reading comprehension workshops based on the cognitive language learning approach not only to improve students' reading skills but also their autonomy through the use of learning strategies. The data were collected from field notes, artifacts, progress reviews, surveys, and photographs.  Este artículo informa sobre un proyecto de investigación cualitativa que propone mejorar la comprensión de lectura y el vocabulario de estudiantes universitarios de inglés que se especializan en temas relativos a explosivos en una escuela de policía, en Colombia. Por tratarse de un curso de inglés específico que carece de los recursos didácticos apropiados, diseñé seis talleres de comprensión de lectura basados en el enfoque del aprendizaje cognitivo de la lengua, para mejorar tanto su comprensión de lectura como su autonomía para usar estrategias de aprendizaje. Para la recolección de datos se emplearon notas de campo, artefactos, pruebas de progreso, encuestas y fotografías.